Pengaruh Tepung Beras Merah (Oryza Nivara) dan Tepung Mocaf (Modified Cassava Flour) terhadap Indeks Glikemik dan Kandungan Gizi Cookies - Utami, Padilla Nur; Farida, Eko (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Diabetes mellitus is a non-communicable disease whose prevalence is increasing every year. Riskesdas data recorded a relatively high increase in prevalence of 1.6% from 6.9% in 2013 to 8.5% in 2018. Lifestyle including fondness for consuming snacks is one of the causes of the high prevalence of diabetes mellitus in Indonesia. The purpose of this study was to make cookies with a low glycemic index formulation of brown rice flour and mocaf flour. Methods: Experimental study with the Quasi-experimental Design. The independent variable is the formulation of cookies and dependent variables include glycemic index and nutrient content. This study uses 3 formulations of cookies 65% : 35%, 75% : 25% and 85%: 15%. Analysis of glycemic index values using IAUC (incremental area under the curve). Nutrient content analysis using One-Way Anova and tukeys. Result: The whole formulation of cookies has a low glycemic index of 25,77-31,24. In 100 g of cookies F1 F2 and F3 contains 26,13–26,58 g fat. Protein as much as 5.14–6.06 g, carbohydrates 62.35 – 64.76 g and fiber 2.24-4.56 g. Conclusion: There is no difference in glycemic index and protein values. But there are differences in the content of fats, carbohydrates and fiber.